Dynamics of platelet ultrastructural changes under correction of arterial blood pressure with losartan in patients with diabetes mellitus in a subcompensation. - Pertseva, N. O. (Морфологія / Morphologia / Morfologìâ, 2012)
We have conducted a quantitative evaluation of ultrastructural changes in the dynamics of platelets in the patients with diabetes mellitus type 2 in a subcompensation phase with arterial hypertension under correction of arterial blood pressure with losartan and with considering of microalbuminuria. It is shown that in the patients without the renal complications observed a damage of thrombocyte hemostasis, as a result of this is a significant increase in the relative amount of activated platelets with rising of content degranulated forms with an imbalance of granules and reduction of the mitochondrial apparatus.Inclusion of losartan in the treatment makes it possible to reduce the degree of ultrastructural disorders of platelets from the 6th month of the treatment. In the patients with microalbuminuria showed a strong damage of thrombocyte hemostasis due to significant growth in the content of the activated, degranulated and aggregated forms of platelets and development of hyperactivation ofplateletsbyhyalinetype. The standard treatment for one year is accompanied by increasing imbalance of granulomer of most platelets and the degree of the heteromorphic pool with a higher content of degranulated and aggregated forms. Losartan usage limits the enlargement of ultrastructural disorders and leads to significant reduction of platelet degranulation.